Pemanfaatan Tanaman Herbal dalam Pembuatan Lilin Aromaterapi di Desa Sungai Majo Pusako - Mhd. Andry Kurniawan; Ledy Pretty Nainggolan; Elisabeth Merba Ria Sibagariang; Dimas Perwandi; Adinda Azahra; Rizky Aditya Reno; Nurul Ummi Khairo; Dimas Wahyudi; Sabrina Inaya Salsabila; Fakhrul Razif; Cinta Setiawati (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
This study aims to utilize herbal plants as the base material for making aromatherapy candles in Desa Sungai Majo Pusako, focusing on education, simulation, and demonstration of candle-making. The activity involves local women as participants who are taught about the benefits of aromatherapy candles, production techniques, and practical applications of herbal plants such as lime, cinnamon, and clove. The training results show that participants can practice making candles using herbal plants that were previously underutilized. The enhancement of skills and knowledge has increased awareness of the health and environmental benefits of aromatherapy candles and opened new business opportunities that can improve local income and economic welfare. Evaluation indicates that while there are challenges in producing high-quality candles, the activity has successfully encouraged innovative and creative thinking in utilizing natural resources. The strengths of the activity include practical skill development and economic opportunities, whereas its weaknesses lie in limited resources and initial participant knowledge. The findings suggest significant potential for developing environmentally friendly herbal-based candle products in the future.